Directed transport induced by α-stable Lévy noises in weakly asymmetric periodic potentials - Risau Gusman, Sebastian Luis; Ibáñez, Santiago Agustín; Bouzat, Sebastian (American Physical Society, 2013)
Fil: Risau Gusman, Sebastian Luis. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina